(untitled) (Innovative professional education, 2023)
The activities of the centers of vocational excellence (CoVEs) in the conditions of public-private partnerships at the level of vocational education and training in Finland are analyzed. A conclusion was made about the effectiveness of such centers. Finland’s experience demonstrates their advantages as advanced, progressive and innovative educational hubs. These are the latest educational environments with state-of-the-art material and technical facilities and inclusive premises. They are effective bridges for providing certain services to governments, employers, employee associations, educational institutions of various levels, etc.; have effective multi-channel funding sources (state, international grants, private individuals or enterprises, donor organizations); have effective management mechanisms due to the involvement of all interested parties (state, business, public) in management.